Alzheimer’s Disease and Porphyromonas gingivalis: Exploring the Links - Ivana Shawkatova; Vladimira Durmanova; Juraj Javor (Life)
Recent research highlights compelling links between oral health, particularly periodontitis, and systemic diseases, including Alzheimer’s disease (AD). Although the biological mechanisms underlying these associations remain unclear, the role of periodontal pathogens, particularly Porphyromonas gingivalis, has garnered significant attention. P. gingivalis, a major driver of periodontitis, is recognized for its potential systemic effects and its putative role in AD pathogenesis. This review examines evidence connecting P. gingivalis to hallmark AD features, such as amyloid β accumulation, tau hyperphosphorylation, neuroinflammation, and other neuropathological features consistent with AD. Virulence factors, such as gingipains and lipopolysaccharides, were shown to be implicated in blood–brain barrier disruption, neuroinflammation, and neuronal damage. P. gingivalis-derived outer membrane vesicles may serve to disseminate virulence factors to brain tissues. Indirect mechanisms, including systemic inflammation triggered by chronic periodontal infections, are also supposed to exacerbate neurodegenerative processes. While the exact pathways remain uncertain, studies detecting P. gingivalis virulence factors and its other components in AD-affected brains support their possible role in disease pathogenesis. This review underscores the need for further investigation into P. gingivalis-mediated mechanisms and their interplay with host responses. Understanding these interactions could provide critical insights into novel strategies for reducing AD risk through periodontal disease management.